Structural behavior of composite moment-resisting joints under column-removal scenario - Chen, Kang (2022)
One series of five composite joints with welded connections was tested and the influences of joint type, slab thickness, and number of shear studs were studied. Welded unreinforced flange with bolt web and reduced beam section connections were included. Load-resisting mechanism, failure mode, energy absorption capacity, and development of strains at the beam-column joints were investigated. Furthermore, test results including tying and flexural resistances and rotation capacities of the composite joints were compared with design values from building codes and design guidelines. Performance of welded connections was also compared with pin connections tested by the authors previously. It was found that the applied load was sustained by flexural action before the bottom beam flange fractured from the joint and by catenary action after that. Design flexural resistance and rotation capacity of composite joints with moment-resisting connections could be achieved, but design values of tying resistance could not be achieved owing to partial damage of connections at the initial stage. However, tie force requirements from Eurocode 1 Part 1-7 could be met.